Empirical Evidence for A‐Site Order in Perovskites. Issue 1 (6th October 2016) - Tolman, Kevin; Ubic, Rick; Liu, Bing; Williamson, Izaak; Bedke, Katherine; Nelson, Eric B.; Li, Lan; Chen, Xiang Ming
Abstract : Models for composition–structure relationships are useful in both the lab and industry, yet few exist for perovskites‐containing extrinsic defects or cation ordering. In this work, an empirical model is used to predict the existence of A‐site cation ordering. Specifically, four compositions in the Na(1−3 x )/2 La(1+ x )/2 TiO3 system ( x = 0.0, 0.0533, 0.1733 and 0.225) were synthesized using a conventional solid‐state mixed‐oxide method. The structure of the x = 0 end‐member (Na0.5 La0.5 TiO3 ) has been reported in various space groups, but always with a random distribution of Na + and La 3+ on the A site; however, empirical modeling suggests that it is not only ordered but also that a small volume increase accompanies the ordering process. While no evidence of long‐range A‐site ordering is observed in this composition via X‐ray or neutron diffraction, electron‐diffraction data indicate short‐range ordering of Na + and La 3+ ions, with the degree of cation ordering decreasing (but the scale of ordered domains and degree of vacancy ordering generally increasing) with increasing x . First‐principles calculations via density functional theory support both conclusions that short‐range ordering in Na0.5 La0.5 TiO3 is stable and that it results in a volume increase with respect to the disordered analog. A similar analysis has been conducted for the Li(1−3 x )/2 La(1+ x )/2 TiO3 and Na(1−3 x )/2 La(1+ x )/2 (Mg0.5 W0.5 )O3 solid solutions. These systems provide additional validation of the accuracy and versatility of the empirical modeling method used.